(untitled) (Mantichora. Italian Journal of Performance Studies, 2021)
This paper traces the evolution of the theme of dancing witches in sabbatical rituals in the European imagery of the early modern age, proposing some considerations on the relationship between the iconographic-choreutic sources on witches and the perception that the society of that times had of them. Nowadays, the word ‘sabbath’ immediately evokes an idea – highly influenced by romantic and symbolist iconographies – of witches wildly or seductively dancing in the night. Back then when the concept of the sabbath started rooting in western mentality, though, the image of the dancing witch was quite different and in fact less frequent than today’s stereotype may suggests. In spite of the scarcity of iconographic sources (just about twenty images survived), the Sabbath dance was still a theme of great relevance and symbolic strength, evidently capable of establishing itself in the common sense, in the continental area as well as in the British Isles. In fact, the use of communicative strategies – both verbal and visual – which highlighted the otherness of witches’ gestures, postures and dance patterns, played a role that was anything but marginal in the construction of their identity in opposition to the Christian community. Thus, analyzing the iconographic repertoire of dancing witches as a whole and in the light of the texts and contexts that constituted its background, we can better understand the role played by these key-figures in the shaping of modern imagery and identity.